A two-stage solid-state reaction to lead nickel niobate powders - O. Khamman (2018)
A perovskite phase of Pb(Ni1/3Nb2/3)O3 or PNN powders has been synthesized by a rapid vibro-milling technique. Both NiNb2O6 and Ni4Nb2O9 have been employed as nickel niobate precursors, with the formation of the PNN phase investigated as a function of calcination conditions by DTA and XRD techniques. Morphology and phase composition have been determined via a combination of SEM and EDX techniques. The nickel niobate precursor and calcination condition have been found to have a pronounced effect on the phase and morphology evolution of the calcined PNN powders. It is seen that optimization of calcination conditions can lead to a single-phase PNN in both methods. However, the formation temperature for single-phase PNN powders was lower for the synthetic method employing a NiNb2O6 precursor. Copyright © 2007 MS&T'07®.